2022
DOI: 10.1002/jha2.488
|View full text |Cite
|
Sign up to set email alerts
|

Second malignant neoplasms after treatment of 1487 children and adolescents with acute lymphoblastic leukemia—A population‐based analysis of the Austrian ALL‐BFM Study Group

Abstract: Second malignant neoplasms (SMN) after primary childhood acute lymphoblastic leukemia (ALL) are rare. Among 1487 ALL patients diagnosed between 1981 and 2010 in Austria, the 10-year cumulative incidence of an SMN was 1.1% ± 0.3%. There was no difference in the 10-year incidence of SMNs with regard to diagnostic-, responseand therapy-related ALL characteristics except for a significantly higher incidence in patients with leukocytes ≥50.0 G/L at ALL diagnosis (2.1% ± 1.0% vs. 0% for 20.0-50.0 G/L, and 1.0% ± 0.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Moreover, the factors affecting the survival rate were found to be prednisolone response on day 8, bone marrow response on day 15, remission status on day 33, minimal residual disease, and the final risk group. 13 In our study, patients diagnosed after 5 years of age had significantly worse OS. There was no significant difference in the OS between sexes, patients who received and did not receive RT occurring relapse, received HSCT, and ALL chemotherapy protocols.…”
Section: Discussionmentioning
confidence: 46%
See 4 more Smart Citations
“…Moreover, the factors affecting the survival rate were found to be prednisolone response on day 8, bone marrow response on day 15, remission status on day 33, minimal residual disease, and the final risk group. 13 In our study, patients diagnosed after 5 years of age had significantly worse OS. There was no significant difference in the OS between sexes, patients who received and did not receive RT occurring relapse, received HSCT, and ALL chemotherapy protocols.…”
Section: Discussionmentioning
confidence: 46%
“…A study conducted by Schmiegelow et al 15 reported that from 2000 onwards, the 10-year probability of survival rate was 40.9% for patients diagnosed with an SPM after ALL. In another study by Poyer et al, 13 the 5-year OS was found to be 55% in patients with SPM. In the present study, the 5-year OS rate was 70% for patients diagnosed with an SPM after ALL.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations